Methylglyoxal: An Emerging Signaling Molecule in Plant Abiotic Stress Responses and Tolerance - Hoque, Tahsina S.; Hossain, Mohammad A.; Mostofa, Mohammad G.; Burritt, David J.; Fujita, Masayuki; Tran, Lam-Son P. (Frontiers in Plant Science, 2016)
The oxygenated short aldehyde methylglyoxal (MG) is produced in plants as a by-product of a number of metabolic reactions, including elimination of phosphate groups from glycolysis intermediates dihydroxyacetone phosphate and glyceraldehyde 3-phosphate. MG is mostly detoxified by the combined actions of the enzymes glyoxalase I and glyoxalase II that together with glutathione make up the glyoxalase system. Under normal growth conditions, basal levels of MG remain low in plants; however, when plants are exposed to abiotic stress, MG can accumulate to much higher levels. Stress-induced MG functions as a toxic molecule, inhibiting different developmental processes, including seed germination, photosynthesis and root growth, whereas MG, at low levels, acts as an important signaling molecule, involved in regulating diverse events, such as cell proliferation and survival, control of the redox status of cells, and many other aspects of general metabolism and cellular homeostases. MG can modulate plant stress responses by regulating stomatal opening and closure, the production of reactive oxygen species, cytosolic calcium ion concentrations, the activation of inward rectifying potassium channels and the expression of many stress-responsive genes. MG appears to play important roles in signal transduction by transmitting and amplifying cellular signals and functions that promote adaptation of plants growing under adverse environmental conditions. Thus, MG is now considered as a potential biochemical marker for plant abiotic stress tolerance, and is receiving considerable attention by the scientific community. In this review, we will summarize recent findings regarding MG metabolism in plants under abiotic stress, and evaluate the concept of MG signaling. In addition, we will demonstrate the importance of giving consideration to MG metabolism and the glyoxalase system, when investigating plant adaptation and responses to various environmental stresses.